2001
DOI: 10.1144/petgeo.7.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Application and implication of horizontal well geochemistry

Abstract: This paper describes the application of horizontal well geochemistry for the first time. Closely spaced samples, taken along a horizontal or deviated well path, allow the identification of reservoir compartments. Significant variations in geochemical parameters are related to the field filling and, if they persist over geological time and over tens of metres, should reflect barriers to diffusion and, by inference, possibly also to fluid flow. Two different approaches have been chosen: (a) closely spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Enormous advances in computation speeds increasingly allow data-rich high resolution fluid descriptions to be used in reservoir simulation initializations. Additionally, as high resolution secondary migration modelling tools are developed, detailed descriptions of reservoir fluid composition can be used to calibrate forward reservoir filling models (Wilhelms et al 2001), which may find particular utility when used in conjunction with reservoir characterization studies.…”
mentioning
confidence: 99%
“…Enormous advances in computation speeds increasingly allow data-rich high resolution fluid descriptions to be used in reservoir simulation initializations. Additionally, as high resolution secondary migration modelling tools are developed, detailed descriptions of reservoir fluid composition can be used to calibrate forward reservoir filling models (Wilhelms et al 2001), which may find particular utility when used in conjunction with reservoir characterization studies.…”
mentioning
confidence: 99%
“…Larter and Aplin, 1995;Peters and Fowler, 2002). Till now, reservoir geochemistry has been applied to the following reservoir characterization and management problem: (1) evaluation of hydrocarbon continuity or reservoir compartmentalization (Kaufman et al, 1990(Kaufman et al, , 1997England, 1992, 1994;Hwang and Baskin, 1994;Nederlof et al, 1994Nederlof et al, , 1995Smalley et al, 1995;Smalley and Hale, 1996;Noyau et al, 1997;Beeunas et al, 1999;Edman and Burk, 1999;Westrich et al, 1999;Wilhems et al, 2001;Permanyer et al, 2002Permanyer et al, , 2007Murty et al, 2005;Hossain, 2007;Rein and Schulz, 2007); (2) analysis of commingled oils for production allocation (Kaufman et al, 1987(Kaufman et al, , 1990Nicolle et al, 1997;Bazan, 1998;Chang et al, 2000); (3) identification of wellbore mechanical problems (Halpern, 1995;Hwang and Elsinger, 1995); (4) evaluation of workovers (Kaufman et al, 1997); (5) production monitoring for enhanced oil recovery (Larter and Aplin, 1995;Nicolle et al, 1997;McKinney and Bland, 2003;Weissenburger and Borbas, 2004;Milkov et al, 2007); (6) characterization of reservoir bitumens and tar mats (Pazuki and Nikookar, 2006;Fazlali et al, 2006;Carpentier et al, 2007;Zahedi et al, 2009) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Since then several studies have been published where the use of geochemical methods gives information on production related issues. Examples include the detection of compartmentalisation (Smalley et al, 1995;Levaché et al, 2000;Wilhems et al, 2001), production allocation (Kaufman et al, 1990;Bazan, 1998) and reservoir monitoring (Nicolle et al, 1997). Common for many of these applications is that they rely on compositional heterogeneities in reservoir hydrocarbons, often seen as a result of variations in source rock facies or source rock maturity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this improved stable carbon isotope analysis technology, especially the introduction of online gas chromatography-combustion-isotope ratio-mass spectroscopy has permitted the logging of mud gas isotopes (Ellis et al, 1999). Wilhems et al (2001) discuss the use of headspace gas samples and drill cuttings to identify reservoir compartments in horizontal wells. The method used in that study relies on the theoretical concepts introduced by England et al (1987) that imply hydrocarbon heterogeneities identified over short distances (10 to 100 m) to be indicators of diffusion barriers within the reservoir (Fig.…”
Section: Introductionmentioning
confidence: 99%